2020
DOI: 10.1186/s12916-020-01610-0
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab dose adjustment to improve clinical outcomes of glioblastoma

Abstract: Background: Glioblastoma (GBM) is one of the most aggressive and vascularized brain tumors in adults, with a median survival of 20.9 months. In newly diagnosed and recurrent GBM, bevacizumab demonstrated an increase in progression-free survival, but not in overall survival. Methods: We conducted an in silico analysis of VEGF expression, in a cohort of 1082 glioma patients. Then, to determine whether appropriate bevacizumab dose adjustment could increase the anti-angiogenic response, we used in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Found that anti-angiogenic effect (VEGFA expression levels) the response to treatment in cell culture. This data indicate that bevacizumab can improve clinical results in Glioblastoma therapy (27).…”
Section: Acknowledgmentmentioning
confidence: 68%
“…Found that anti-angiogenic effect (VEGFA expression levels) the response to treatment in cell culture. This data indicate that bevacizumab can improve clinical results in Glioblastoma therapy (27).…”
Section: Acknowledgmentmentioning
confidence: 68%
“…Consistent with this framework, mouse studies have shown dose-dependent effects of bevacizumab on tumor cells and vasculature. 34 , 35 Future studies will need to explore whether shorter-term survivors have fewer VEGFA receptors and would benefit from reduced bevacizumab dosing to shift tumor physiology from vascular pruning to normalization.…”
Section: Discussionmentioning
confidence: 99%
“…Of primary GBs, 80% were found to express VEGFA. A potential relationship could reveal a subgroup of GB patients who might benefit from a therapy with angiogenesis inhibitors ( 45 ). MPV/PC ratio seems to be a promising biomarker for the activity of platelets.…”
Section: Discussionmentioning
confidence: 99%